Characterization of induced pluripotent stem cell‐derived megakaryocyte lysates for potential regenerative applications. Issue 9 (12th June 2018) - Baigger, Anja; Eicke, Dorothee; Yuzefovych, Yuliia; Pogozhykh, Denys; Blasczyk, Rainer; Figueiredo, Constanca
Abstract: Recently, platelet‐derived growth factors present in lysates became an extreme interest in the field of regenerative medicine such as in wound healing and as substitutes to foetal bovine serum in xeno‐free cell culture systems. However, the generation of such platelet lysates completely depends on the availability of platelet donors. In this study, the possibility to use in vitro ‐generated megakaryocytes derived from induced pluripotent stem cells (iPSCs) as a cell source for typical platelet growth factors was investigated. Therefore, the presence and levels of those factors were characterized in in vitro ‐produced megakaryocytes. In comparison with platelets, in vitro ‐generated megakaryocytes showed a multifold increased content in transcript and protein levels of typical platelet growth factors including platelet‐derived growth factors (PDGFs), transforming growth factor (TGF)‐1β, vascular endothelial cell factor (VEGF)‐A, epidermal growth factor (EGF), insulin‐like growth factor (IGF)‐1 and tissue factor (TF). Hence, iPSC‐derived megakaryocytes may serve as an efficient cell source for a donor‐independent generation of growth factor‐rich lysates with a broad application potential in innovative cell culture systems and regenerative therapies.